Preliminary study of endovascular intervention for cephalic arch stenosis under ultrasonic guidance with radiography - Zhang Li-hong; Zhan Shen; Xiao Guang-hui; Wang Yu-zhu (Linchuang shenzangbing zazhi)
ObjectiveTo summarize the clinical experiences of endovascular treatment of cephalic arch stenosis under ultrasonic guidance with radiograph.MethodsFrom January 2017 to December 2020，clinical data were reviewed for patients of arteriovenous access malfunction and cephalic arch stenosis.Endovascular intervention was performed for cephalic arch stenosis under ultrasonic guidance with radiography.Retrospective analysis was performed for patient profiles，access information and intraoperative findings.And angiographic follow-ups were conducted for postoperative patency at 180 days.Primary endpoint was operative success rate while secondary endpoints included complication rates，postintervention primary patency rate and primary assisted patency rate of arteriovenous access at Day 180.ResultsIn patients of arteriovenous access with cephalic vein as a single outflow tract，the incidence of cephalic arch stenosis was 9.7%（48/495）.Clinical manifestations included prolonged hemostasis time （n=22），prolonged hemostasis time plus progressive tumor enlargement （n=16），prolonged hemostasis time plus elevated venous pressure （n=8） and routine angiography （n=2） after thrombectomy of arteriovenous grafts.Technical success rate was 100%，clinical success rate 100% and complication rate 8.33%.All instances were vascular rupture.Radiation time was 3.8（2.4，6.3） min and radiation dose 77.4（42.7-159.6） mGy during treatment.And 180-day primary patency rate was 22.91%，primary assisted patency rate 97.92% and cumulative patency rate 97.92%.ConclusionEndovascular treatment of cephalic arch stenosis under ultrasonic guidance with radiography offers a high technical success rate，a high short-term patency and a low complication rate.It is worthy of clinical popularization.